Variations in national availability of waivered buprenorphine prescribers by racial and ethnic composition of zip codes - Katherine A. Hirchak; Solmaz Amiri; Gordon Kordas; Oladunni Oluwoye; Abram J. Lyons; Kelsey Bajet; Judith A. Hahn; Michael G. McDonell; Aimee N. C. Campbell; Kamilla Venner (BMC, 2022)
Abstract Background Opioid overdose remains a public health crisis in diverse communities. Between 2019 and 2020, there was an almost 40% increase in drug fatalities primarily due to opioid analogues of both stimulants and opioids. Medications for opioid use disorder (MOUD; e.g., buprenorphine) are effective, evidence-based treatments that can be delivered in office-based primary care settings. We investigated disparities in the proportion of national prescribers who have obtained a waiver issued to prescribe MOUD by demographic characteristics. Methods Data for the secondary data analyses were obtained from the Drug Enforcement Administration that maintains data on waivered MOUD prescribers across the US. Proportion of waivered prescribers were examined by ZIP code, race and ethnicity composition, socioeconomic status, insurance, and urban-rural designation using generalized linear mixed effects models. Results Compared with predominantly Non-Hispanic White ZIP codes, other racially and ethnically diverse areas had a higher proportion of waivered buprenorphine prescribers. Differences in prescriber availability between predominant racial group was dependent on rurality based on the interaction found in our fitted model. In metropolitan areas, we found that predominantly Non-Hispanic White ZIP codes had a lower rate of waivered prescribers compared to predominantly Black/African American ZIP codes. Conclusions Our findings suggest that among AI/AN and Black/African American neighborhoods, availability of waivered prescribers may not be a primary barrier. However, availability of waivered prescribers and prescribing might potentially be an obstacle for Hispanic/Latinx and rural communities. Additional research to determine factors related to improving MOUD availability among diverse communities therefore remains vital to advancing health equity.